Extraction of Carotenoids from Pumpkin (Cucurbita moschata) and Spinach (Spinacia oleracea) Using Environmentally Friendly Deep Eutectic Solvents (DESs) - Koray Tanrıver; Mehmet Bilgin; Selin Şahin Sevgili; İrem Toprakçı Yüksel; Ebru Kurtulbaş Şahin (AppliedChem)
The annually wasted amount of food has surpassed 1 billion metric tons. Food waste is considered as an important source for the recovery of bioactive compounds, such as carotenoids. There is a demand for antioxidants, nutraceuticals and natural colorants in various industries and carotenoids are one of the commonly used compounds that fit this description. Pumpkin and spinach waste, whose combined amount is over 2 million metric tons, contains bioactive compounds and these wasted foods could be utilized for the recovery of carotenoids. Carotenoids are hydrophobic molecules; therefore, commercial extraction processes often use highly non-polar solvents, and these are rarely environmentally friendly. The aim of this research was to develop effective extraction processes for carotenoids from pumpkin and spinach using environmentally friendly green chemicals. A series of deep eutectic solvents (DESs) composed with L-menthol and carboxylic aliphatic acids were made for the extraction of carotenoids from pumpkin (Cucurbita moschata) and spinach (Spinacia oleracea) via mechanical mixing–assisted extraction (MMAE) and homogenization-assisted extraction (HAE). Response surface methodology (RSM) and analysis of variance (ANOVA) were used to analyze the data and optimization. The DESs composed from L-menthol and propionic acid had the best effect on the extraction of total carotenoid content (TCC) (represented as β-carotene) from pumpkin and spinach via solutions with 1:2 and 1:4 molar ratios, respectively. The yield of carotenoid extraction is expressed in μg-β-carotene/g of pumpkin or spinach. Under the calculated optimum conditions, the yields are estimated to be 11.528 μg-β-carotene/g-pumpkin for the MMAE method, 8.966 μg-β-carotene/g-pumpkin for the HAE method, 16.924 μg-β-carotene/g-spinach for the MMAE method and 18.870 μg-β-carotene/g-spinach for the HAE method.